Effect Various Combination of Organic Waste on Compost Quality - Hapsoh, .; Gusmawartati, .; Yusuf, Muhammad (UNIVERSITY OF LAMPUNG, 2015)
Municipal solid waste and agricultural waste have different ratio C/N and nutrients contents. They can be used as compost row materials. The purpose of the research was to get an optimum combination of both wastes to improve compost quality, to meet the Indonesian National Standard 19-7030-2004. Composting process use pots. The treatments were twelve combination of municipal solid waste (garbage market, household waste, restaurant waste) and agricultural waste (rice straw, empty fruit bunches of oil palm, cassava peel, banana skin) with a ratio of 1:1 and enriche by chicken manure, cow manure, wood ash and cellulolytic microorganisme. The treatment were replicated three times. The results showd that the nutrients content of compost were 0.77 to 1.19% nitrogen, 0.23 to 0.30% phosphorus, 0.46 to 0.69% potassium and 15.48 to 34.69% organic matter. The combination of agricultural waste and municipal solid waste affected the quality of compost. Compost that meets SNI 19-7030-2004 is a combination of rice straw+market waste that contains 1.12% nitrogen, 0.28% phosphorus, 0.63% potassium, ratio C/N 19.50, pH 7.42, and organic matters 37.65%. [How to Cite: Hapsoh, Gusmawartati, and M Yusuf. 2015. Effect Various Combination of Organic Waste on Compost Quality. J Trop Soils 19: 59-65. Doi: 10.5400/jts.2015.20.1.59][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.59]